Children of mentally III parents at risk evaluation (COMPARE): design and methods of a randomized controlled multicenter study - part I - Christiansen, Hanna; Zietlow, Anna-Lena; Krisam, Johannes; Klose, Christina; Kieser, Meinhard (Frontiers in psychiatry, 2019)
Objectives: Mental disorders are frequent, associated with disability-adjusted life years, societal and economic costs. Children of parents with a mental illness (COPMI) are at an increased risk to develop disorders themselves. The transgenerational transmission of mental disorders has been conceptualized in a model that takes parental and family factors, the social environment (i.e. school, work, social support), parent-child-interaction and possible child outcomes into account. The goal of the “Children of Mentally Ill Parents At Risk Evaluation” (COMPARE) study will thus be twofold: 1) to establish the efficacy and cost-effectivness of a high-quality randomized controlled trial (RCT) with the aim of interrupting the intergenerational transmission of mental disorders in COPMI; 2) to test the components of the trans-generational transmission model of mental disorders. Methods: To implement a randomized controlled trial (RCT: comparison of parental cognitive behavioural therapy/CBT with CBT + Positive Parenting Program) that is flanked by four add-on projects that apply behavioral, psychophysiological, and neuro-imaging methods to examine potential moderators and mediators of risk transmission (projects COMPARE-emotion/-interaction/-work/-school). COMPARE-emotion targets emotion processing and regulation and its impact on the transgenerational disorder transmission; COMPARE-interaction focuses especially on the impact of maternal comorbid diagnoses of depression and anxiety disorders and will concentrate on different pathways of the impact of maternal disorders on socio-emotional and cognitive infant development, such as parent-infant interaction and the infant's stress regulation skills. COMPARE-work analyzes the transmission of strains a person experiences in one area of life to another (i. e. from family to work; spill-over), and how stress and strain are transmitted between indivuduals (i. e. from parent to child; cross-over). COMPARE-school focuses on the psychosocial adjustment, school performance, and subjective well-being in COPMI compared to an adequate control group of healthy children. Results: This study protocol reports on the interdisciplinary approach of COMPARE testing the model of the transgenerational transmission of mental disorders. Conclusion: The combination of applied basic with clinical research will facilitate the examination of specific risk transmission mechanisms, promotion, dissemination and implementation of results into a highly important but largely neglected field.